Clinical and pathological characteristics of multiple primary malignant neoplasms cases. Issue 11 (21st August 2021) - Si, Lixiang; Feng, Yuxu; Wang, Yajing; Zhong, Jie; Sun, Zijian; Li, Xiaoyou; Sun, Yan
Abstract: Objectives: To investigate the clinical and pathological features of multiple primary malignant neoplasms (MPMNs) cases. Methods: The clinical data of 24 105 tumour patients admitted to Jiangsu Cancer Hospital in 2018 were retrospectively reviewed, and 270 patients with MPMNs were selected as the research subjects. Among them, 101 cases of synchronous carcinoma (SC) and 92 cases of metachronous carcinoma (MC) were divided into groups for statistical analysis. Univariate and multivariate cox regression analyses were conducted using SPSS 22.0 software. Results: Among 24 105 cases, there was a male‐to‐female ratio of 1.45:1. Compared with MC cases, SC patients have a higher proportion of male cases. Primary neoplasms in gastric cancer, head and neck cancer, oesophageal cancer and colon cancer occupied most cases in male MPMNs, while primary breast cancer ranked first in female MPMNs. In addition, the leading secondary neoplasms were duodenal carcinoma, lung cancer and male MPMNs and lung cancer in female MPMNs. As for SC MPMNs, primary neoplasms were occupied by lung cancer, gastric cancer and oesophageal cancer, while the secondary neoplasms were mostly consisted of oesophageal cancer and lung cancer. Finally, the MC MPMNs were mostly consisted of breast cancer and gastric cancer as primary neoplasms, while lung cancer and oesophageal cancer as secondary neoplasms. Conclusions: Screening for primary cancer should be strengthened over the age of 50 years for male patients with gastric cancer or female patients with breast cancer to reduce or monitor the occurrence of MPMNs.